Book Review: Gennaro Ferrara and Alfonso Morvillo (eds.) Training in Logistics and the Freight Transport Industry - Vanelslander, Thierry (European Journal of Transport and Infrastructure Research, 2004)
This book was meant to disseminate the results of a national research project funded by the European Union. In this case, a standard structure could be expected containing the need for and the context of the research, the methodology used and the results obtained. But the book does a lot more than summarizing the research conducted. Each of the traditional items are of course reported throughout the different articles, but the emphasis is on original and provocative approaches. The evaluation of the latest trends in the sector, the impact of education and training on sector behaviour, the impact of culture, and the monitoring of reproductability and transferability of the evaluation procedure give an extra dimension to the analysis reporting. The main topic in itself too merits attention and praise since there is ample supply of training programmes, the quality of which, however, varies (a program useful in one situation may not apply to or even have a counterproductive effect in a different situation, and the need for training should be clearly evaluated before taking any action).